First occurrence of Schistostemon (Urb.) Cuatrec. (Humiriaceae) in states of Roraima and Pará, Brazil - Holanda, Ana Sofia Sousa de; Zartman, Charles Eugene; Hopkins, Michael John Gilbert; Valsko, Jefferson José; Krahl, Amauri Herbert (Check List, 2015)
Schistostemon is recorded for the first time in the States of Roraima and Pará extending its distribution to a new northern limit within Brazilian territory. © 2015 Check List and Authors.